2020
DOI: 10.1093/mnras/staa3376
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of globular clusters within their parent galaxies: multiple stellar populations and internal kinematics

Abstract: Using three-dimensional smoothed particle hydrodynamical simulations, we investigate the formation of multiple stellar populations (MSPs) in globular clusters (GCs) within the context of their parent galaxies. In our scenario, the second generation of stars (2G) originate from both asymptotic giant branch (AGB) polluters and pristine gas accreted from the host galaxy. Previous theoretical and numerical studies have demonstrated that this “AGB with dilution” model has the potential to alleviate several problems… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 133 publications
2
17
1
Order By: Relevance
“…For example, it is not possible for the present study to investigate how the binary status of the simulated SCs can evolve over the next 2 Gyr (to the present time); will they merge to form a single SC, or not. We also cannot comment on how the simulated rotation can be less remarkable due to the two-body dynamical relaxation effects, and whether or not ISM can be accreted onto the new SCs to form new SCs, as discussed in recent papers (e.g., McKenzie & Bekki 2021a). We need to improve our modeling in star formation within GMCs, including more realistic feedback effects from massive stars with different masses (including supernovae).…”
Section: Future Work: From Sc Formation To Long-term Evolutionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, it is not possible for the present study to investigate how the binary status of the simulated SCs can evolve over the next 2 Gyr (to the present time); will they merge to form a single SC, or not. We also cannot comment on how the simulated rotation can be less remarkable due to the two-body dynamical relaxation effects, and whether or not ISM can be accreted onto the new SCs to form new SCs, as discussed in recent papers (e.g., McKenzie & Bekki 2021a). We need to improve our modeling in star formation within GMCs, including more realistic feedback effects from massive stars with different masses (including supernovae).…”
Section: Future Work: From Sc Formation To Long-term Evolutionmentioning
confidence: 97%
“…We have already investigated a number of key physical processes related to SC formation such as GMC collisions during the LMC-SMC collision (e.g., Bekki et al 2004), gas accretion onto SCs (e.g., Bekki & Mackey 2009;Armstrong et al 2018), new star formation within massive globular clusters accreting gas from ISM (e.g., McKenzie & Bekki 2018;McKenzie & Bekki 2021a), and the roles of gas infall from the SMC to the LMC in SC formation (Bekki & Chiba 2007b;Tsuge et al 2019). We have not yet investigated the entire formation processes of SC formation from their natal GMCs.…”
mentioning
confidence: 99%
“…However, as it has been discussed in Section 1, the AGB ejecta alone are not able to reproduce the observed SG abundance patterns therefore they are generally assumed to be diluted with pristine gas. As in C19, we assume that the cluster is moving into a background distribution of gas representing the disk of a star-forming high-redshift galaxy (Kravtsov & Gnedin 2005;Bekki 2012;Kruijssen 2015;McKenzie & Bekki 2021). The consequence of this motion is an asymmetric accretion of gas on the system from the side toward which the cluster is moving (Naiman et al 2011).…”
Section: Simulation Set-upmentioning
confidence: 99%
“…Another avenue are the much closer giant globular clusters 47 Tucanae (47 Tuc) and Omega Centauri Cen), also known as NGC 5139. These objects have distances of 4.4 and 5.5 kpc, respectively (Chen et al 2018; Del Principe et al 2006) and may be the nucleated remnants of ancient tidally-stripped dwarf galaxies (Peebles 1984; Norris et al 1996; Hilker & Richtler 2000; Bekki & Norris 2006; Lee et al 2009; McKenzie & Bekki 2021) and therefore in possible possession of a dark matter core. Various authors have suggested the role that dark matter may play in explaining their velocity dispersion profiles (e.g.…”
Section: Introductionmentioning
confidence: 99%